2023
DOI: 10.1186/s12871-023-02083-3
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus video-assisted laryngoscopy for perioperative endotracheal intubation (COVALENT) - a randomized, controlled multicenter trial

Abstract: Background Data on the routine use of video-assisted laryngoscopy in peri-operative intubations are rather inconsistent and ambiguous, in part due to small populations and non-uniform outcome measures in past trials. Failed or prolonged intubation procedures are a reason for relevant morbidity and mortality. This study aims to determine whether video-assisted laryngoscopy (with both Macintosh-shaped and hyperangulated blades) is at least equal to the standard method of direct laryngoscopy with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It offers clinicians a clearer view of the airway structures and enables better alignment and positioning of the ETT, ultimately enhancing the overall effectiveness of endotracheal intubation. Furthermore, the current guideline for prehospital emergency anesthesia with endotracheal intubation also recommends the utilization of VL [7]. A trial conducted in 2016 also demonstrated that VL exhibited a higher rate of successful first-attempt intubation in emergency situations or among patients admitted to the ICU as compared to the use of a DL [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It offers clinicians a clearer view of the airway structures and enables better alignment and positioning of the ETT, ultimately enhancing the overall effectiveness of endotracheal intubation. Furthermore, the current guideline for prehospital emergency anesthesia with endotracheal intubation also recommends the utilization of VL [7]. A trial conducted in 2016 also demonstrated that VL exhibited a higher rate of successful first-attempt intubation in emergency situations or among patients admitted to the ICU as compared to the use of a DL [8][9][10].…”
Section: Introductionmentioning
confidence: 99%